ENHANCING PERSONALIZED LANGUAGE LEARNING THROUGH ARTIFICIAL INTELLIGENCE: OPPORTUNITIES AND CHALLENGES - Veronica Khatamova; Moxigul Xamidjonova (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
Artificial intelligence (AI) is reshaping language education by enabling personalized, adaptive, and data-driven learning experiences. This paper explores how AI supports individual language learners through adaptive content, real-time feedback, and autonomy. It also analyzes key platforms and discusses limitations related to ethics, data privacy, and human interaction. A blended learning model that combines AI tools with human guidance emerges as the most effective. The study concludes that AI has the potential to democratize access to high-quality language education, but its implementation must be ethical, inclusive, and pedagogically sound.